PERAN GURU AKIDAH AKHLAK DALAM MEMBINA AKHLAK PESERTA DIDIK DI KELAS IX A MTS NEGERI 1 CILACAP KABUPATEN CILACAP PROVINSI JAWA TENGAH - resti, Imam Muzaki Ulfi (UNISAN JURNAL, 2024)
This research is about the role of the Aqidah Akhlak teacher in developing student morals at MTs Negeri 1 Cilacap. The role of a teacher of moral beliefs is so important. Apart from the role as a role model, moral aqidah teachers must have good temperament because their behavior is indirectly highlighted by students. The purpose of this research is to determine the role of moral belief teachers in forming the character of students in class IX A MTs Negeri 1 Cilacap, and the factors that influence the formation of students’ character. This type of research is qualitative descriptive research. There are several methods for collecting data, namely, observation, interviews and documentation. The steps taken are data reduction, data display (data presentation), verification (drawing conclusions). From the data collected, the author analyzes it using inductive thinking which starts from a specific conclusion and then becomes a conclusion. Results of research on the role of moral belief teachers as educators, as role models, as advisors. Supporting factors: parental love and appreciation factors. Inhibiting factors are lack of parental love and the influence of friends. Conclusion The role of a teacher of moral beliefs is: 1. as an educator, 2. as a role model 3. as an advisor. The character values instilled by teachers in students in class IX A MTs Negeri 1 Cilacap are: 1) religious values, 2) honesty values, 3) discipline values, 4) responsibility values. Factors that influence the formation of students’ character in class IX A MTs Negeri 1 Cilacap consist of two factors, namely supporting and inhibiting factors. Supporting factors are the influence of the students’ parents’ love and appreciation. The inhibiting factor is the lack of love from parents and friends/social relations.